EFFECT OF POST HEAT TEMPERATURE TO HARDNESS AND MACROSTRUCTURE IN WELDED STELL ST 37 - - Subardi; Djoko Suprijanto; Roza Lyndu R. Mahendra (Universitas Muhammadiyah Semarang, 2009)
The present study aims to investigate the effect of post heat temperature of hardness andmacrostructure on the result steel welded St 37. Welded process with SMAW (Shelded Metal ArcWelding) and AC-DC current. Plate steel ST 37 welded of longitudinal, than heat treatment withtemperature various: 300°C, 400°C dan 500°C.Highest rate hardness 157,83 kg/mm2 on temperature treatment spesiment 500o cause haveferit grain boundary structure more and homogen so properties more hardness. The lows bendingstrength 43,51 kg/mm2 on raw material, cause have ferit structure and perlit so more soft properties.The micostuctrure welded area arround; ferit graind boundary, ferit widmanstatten, ferit acicularand perlit.